2009
DOI: 10.4142/jvs.2009.10.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Modification of pharmacokinetics of norfloxacin following oral administration of curcumin in rabbits

Abstract: Investigation was carried out in adult New Zealand white rabbits to study the influence of curcumin pre-treatment on pharmacokinetic disposition of norfloxacin following single oral administration. Sixteen rabbits were divided into two groups of eight each consisting of either sex. Animals in group-I were administered norfloxacin (100 mg/kg body weight p.o), while animals in group-II received similar dose of norfloxacin after pre-treatment with curcumin (60 mg/kg body weight per day, 3 days, p.o). Blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 18 publications
(27 reference statements)
2
22
3
Order By: Relevance
“…Pavithra et al [22] reported that prior treatment of curcumin (60 mg kg -1 , PO) for 3 days significantly increased elimination half-life and volume of distribution of norfloxacin, a reported CYP1A2 inhibitor, in rabbits.…”
Section: Resultsmentioning
confidence: 98%
“…Pavithra et al [22] reported that prior treatment of curcumin (60 mg kg -1 , PO) for 3 days significantly increased elimination half-life and volume of distribution of norfloxacin, a reported CYP1A2 inhibitor, in rabbits.…”
Section: Resultsmentioning
confidence: 98%
“…After oral curcumin pretreatment for 3 days in rabbits, single oral dose norfloxacin pharmacokinetics were significantly modified compared with those in the non-pretreated group. Mean absorption half-life was decreased (by 23%) while increases were seen in the absorption rate constant (by 41%), t½ (by 19%), AUC (by 52%), AUC (first moment) (by 69%), mean residence time (by 12%), and Vd (area) (by 31%) (all p < 0.05) [308].…”
Section: Metabolism Interactionsmentioning
confidence: 95%
“…Thus, the modulation of P-gp or CYPs or UGTs may affect the pharma- Curcumin has been demonstrated to down regulate the P-gp levels in rat, 16,26) and the cell-based assay using rhodamine 123 indicated that curcumin significantly inhibited the activity of P-gp with a decrease in P-gp protein and multidrug resistance gene MDR1 mRNA levels. Referring to the studies, 22,27) pretreatment with curcumin could alter the oral bioavailability of docetaxel and norfloxacin, which are substrates of P-gp. Therefore, the improved absorption of losartan caused by inhibition of P-gp is likely to result in higher increased AUC and C max .…”
Section: Discussionmentioning
confidence: 99%